Career Preferences and Choices Among Medical and Dental Students: A Study from a Public Sector Medical College in Rawalpindi - Saeed, Farrukh; Rashid, Amir; Farhat, Kulsoom; Khan, Hammad Gul; Naveed, Tahir (Pakistan Armed Forces Medical Journal, 2025)
Objective: To investigate reasons for choosing medical profession, preferences among different specialties as career choice, and willingness to choose medical profession again, if given another chance, among medical (MBBS) and dental (BDS) students at a public sector medical college. Study Design: Analytical cross-sectional. Place and Duration of Study: Army Medical College, Rawalpindi, Pakistan, from Dec 2022 to Feb 2023. Methodology: A total of 1117 (925 MBBS and 192 BDS) students were included in this study. They answered a questionnaire about their motivations for choosing medicine and their preferred specialty out of a provided list (22 specialties for MBBS and 10 for BDS). Data was analyzed using IBM SPSS version 22.0. Results: Majority of students (340, 30.4%) chose medical professional for better lifestyle, high financial gains (204, 18.3%), and respect in society (182, 16.3%). There was a statistically significant relationship found between the reasons for joining medical professional and students of MBBS and BDS (p-value<0.001). Conclusions: These findings highlight the prominent role of extrinsic rewards and perceived social status in shaping career preferences among medical and dental undergraduates. The most frequently cited determinant of specialty selection among students in this cohort was the expectation of lucrative financial prospects and a secure future, with respect and social prestige also serving as important motivating factors.